HUBUNGAN ANTARA DEKOMPOSISI DAN PELEPASAN NITROGEN SISA TANAMAN DENGAN DIVERSITAS MAKROFAUNA TANAH - Sugiyarto Sugiyarto; M.P. Setyaningsih (BUANA SAINS, 2007)
A comparative study of decomposition rate and nitrogen release of crop residues of ‘nanas’ (Ananas commosus), ‘kimpul’ (Xanthosoma sagittifolium) and ‘kapulaga’ (Amomum cardomomum) as well as their relationships to soil macrofauna diversity was conducted in permanent boxes containing soils. Soil macrofauna used for this study were Pheretima sp, Phyllophaga sp., Lithobius sp., Calosoma sp., Blatta sp., Lycosa sp., and Narceus sp. which were previously acclimated for 2 days. Results of this study showed that the highest rate of decomposition occurred on organic matter generated from ‘kimpul’, followed by ‘nanas’ and ‘kapulaga’. The highest rate of nitrogen release was observed for organic matter generated from ‘kimpul’, followed by ‘kapulaga’ and ‘nanas’. Both rate of decomposition or rate of nitrogen release positively correlated with diversity index value of soil macrofauna